Thighplasty for Transfemoral Amputations and Osseointegration: Lower Rate of Complications Than Thighplasty for Body Contouring - Hannah P. Gibbs, MD; Ashley B. Anderson, MD; Benjamin W. Hoyt, MD; Ean R. Saberski, MD; Jonathan A. Forsberg, MD, PhD; Jason M. Souza, MD; Benjamin K. Potter, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Modern techniques in lower extremity amputation have made significant advances to improve prosthetic control and soft-tissue envelopes through various techniques, including medial thighplasties. These advances are necessary to enhance the fit and functionality of the prosthesis in transfemoral amputations. Methods:. We performed a retrospective review of all thighplasties performed at our institution in patients with ipsilateral transfemoral amputation from November 2017 to December 2021. We recorded complication rates, types of complications, and treatments throughout this period, and compared it to thighplasty for cosmetic surgery patient outcomes. Univariate statistics were performed using the Student t test and χ2 analysis to identify differences between the complication and no-complication cohorts, as well as for comparison with published, historical, bariatric surgery, and cosmetic thighplasty controls. Results:. There were 46 combined thighplasty and osseointegration procedures, and 12 thighplasty procedures alone, and all patients had a minimum 2-year follow-up. The mean follow-up was 3.39 (2.10–4.05) years. In total, 13 (22%) patients developed a complication: 8 (57%) were due to dehiscence, 2 (14%) were due to seroma, 2 (14%) were due to superficial infection, and 1 (7%) was due to deep infection. Overall, our rate of complication was significantly lower than the overall historical complication rate (22% versus 68%, P < 0.0001). Conclusions:. We demonstrate herein that the overall complication rate for thighplasty undertaken to improve thigh contour and bulk in transfemoral amputees is lower than when thighplasty is undertaken for other indications.